Theoretical and Experimental Vibrational Characterization of Biologically Active Nd(III) Complex - Irena Kostova; Jan Mojžiš; Vasile Chiş (Molecules, 2021)
The neodymium(III) complex of orotic acid (HOA) was synthesized and its structure determined by means of analytical and spectral analyses. Detailed vibrational analysis of HOA, sodium salt of HOA, and Nd(III)–OA systems based on both the calculated and experimental spectra confirmed the suggested metal–ligand binding mode. Significant differences in the IR and Raman spectra of the complex were observed as compared to the spectra of the ligand. The calculated vibrational wavenumbers, including IR intensities and Raman scattering activities, for the ligand and its Nd(III) complex were in good agreement with the experimental data. The vibrational analysis performed for the studied species, orotic acid, sodium salt of orotic acid, and its Nd(III) complex helped to explain the vibrational behaviour of the ligand’s vibrational modes, sensitive to interaction with Nd(III). In this paper we also report preliminary results about the cytotoxicity of the investigated compounds. The cytotoxic effects of the ligand and its Nd(III) complex were determined using the MTT method on different tumour cell lines. The screening performed revealed that the tested compounds exerted cytotoxic activity upon the evaluated cell lines.